Paraleptopentacta, a new Mediterranean and north-west Atlantic sea cucumber genus, with the first record of P. tergestina n. comb. (Echinodermata: Dendrochirotida: Cucumariidae) from the north-western Algerian coast - Mezali, Karim; Thandar, Ahmed S.; Khodja, Ihcene (Zootaxa, 2020)
The genus Leptopentacta H.L. Clark, 1938 is here reviewed and restricted to include only the type species and related tropical Pacific forms, while a new genus Paraleptopentacta is erected to accommodate the Mediterranean and some north-west Atlantic species, formerly assigned to Leptopentacta. Paraleptopentacta n. gen. is characterized by a calcareous ring usually without posteriorly forked radial plates, in combination with body wall ossicles as an external layer of baskets (sometimes absent) and an inner layer of smooth (in one species knobbed), single-layered, multilocular plates, without a reticulum, as opposed to Leptopentacta H.L. Clark, 1938, which always has forked tails to the radial plates and ossicles as an external layer of rosettes and/or baskets and an inner layer of multi-layered or often reticulated scales/plates. A key separating both the genera and their species is provided. In addition, a first record of P. tergestina n. comb. (Sars, 1859), based on individuals collected as bycatch by a commercial benthic trawler in the Mostaganem region, north-west Algeria, is briefly described and its in vitro behavior noted.